Social services utilisation and referrals after seeking help from health services for self-harm: a systematic review and narrative synthesis - Sarah Steeg; Shamini Gnani; Catherine Robinson (BMJ Publishing Group, 2023)
Objectives Suicide prevention is a major public health challenge. Appropriate aftercare for self-harm is vital due to increased risks of suicide following self-harm. Many antecedents to self-harm involve social factors and there is strong rationale for social services-based self-harm aftercare. We aimed to review evidence for social service utilisation and referrals among people seeking help following self-harm.Design Systematic review with narrative synthesis.Data sources PubMed, PsycINFO, AMED, Social Policy and Practice, EMBASE, Medline, Web of Science, Social Care Online, citation lists of included articles and grey literature.Eligibility criteria Studies of people of any age in contact with health services following self-harm, with study outcomes including referrals to or utilisation of social workers and social services.Data extraction and synthesis Information was extracted from each included study using a proforma and quality was critically assessed by two reviewers. Narrative synthesis was used to review the evidence.Results From a total of 3414 studies retrieved, 10 reports of 7 studies were included. Study quality was generally high to moderate. All studies were based in emergency departments (EDs) and most were UK based. In studies based solely on ED data, low proportions were referred to social services (in most studies, 1%-4%, though it was up to 44% when social workers were involved in ED assessments). In one study using linked data, 15% (62/427) were referred to social services and 21% (466/2,205) attended social services over the subsequent 3-year period.Conclusions Overall, few patients were referred to social services after self-harm. Higher reported referral rates may reflect greater service availability, involvement of social workers in psychosocial assessments or better capture of referral activity. Social services-based and integrated approaches for self-harm aftercare are important future directions for suicide prevention. Improved links between social services and health services for people seeking support after self-harm are recommended.